Product Innovation Utilization for building better Sustainable Enterpreneur Performance: Kademangan Villages Community Service Implementation: Product Innovation Utilization for building better Sustainable Enterpreneur Performance: Kademangan Villages Community Service Implementation - Mochamad Soelton (Universitas Warmadewa, 2024)
South Tangerang experienced rapid development of MSMEs after the pandemic, the South Tangerang City Cooperatives and SMEs Service (Tangsel) noted a growing trend in the number of Micro, Small and Medium Enterprises (MSMEs). Data from the South Tangerang City Cooperatives and SMEs Service shows that there were around 40 thousand GENERAL actors, before the pandemic. After the pandemic around 89 thousand. Now it is approaching around 140 thousand. Keranggan Village has a lot of interest in food and beverage products, or it could be said that the sector most involved in by MSME players is culinary. Around 70 percent of MSME players in the culinary sector, starting from roasted nuts, ketapang seeds, banana chips, kembang goyang, and other types of chips. Initially it started with consumption by local people only, but continued to grow outside the Keranggan area, but it is still traditional. Some assistance from the local government and other government institutions to develop MSMEs in Keranggan. There are several superior Keranggan plants that are hampered in their development due to several things, especially supply chain factors, namely the production of roasted peanuts. Several years ago, before the Covid-19 pandemic, these roasted peanuts became a favorite because they entered China, even though they had no product identity. Keranggan roasted peanuts have been famous since the City of South Tangerang was not yet formed. This Keranggan roasted peanut snack tastes different from other roasted peanut snacks. The difference lies in the way it is processed by roasting it using sand, which is its own characteristic. Because the processing method is still traditional, the resulting taste is different from other roasted peanut products. The raw material for peanuts is sent from Central Java and East Java, because in Keranggan there are no residents who grow peanuts because there is no agricultural land anymore. The high cost of raw materials means production is reduced. The results of the production are distributed to stalls and markets around South Tangerang and also marketed to various areas in Jabodetabek.